2013
DOI: 10.1177/1471301213488899
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and dementia: Does artistic activity affect well-being beyond the art class?

Abstract: The Alzheimer's Association's Memories in the Making (MIM) art activity program is intended to enhance the well-being of individuals who are living with dementia. Previous evaluations of MIM have found that participants show benefits on several well-being domains measured by the Greater Cincinnati Chapter Well-Being Observation Tool. The current study extended those findings by looking for evidence of carry-over effects beyond the temporal boundaries of MIM sessions. Additionally, this study evaluated key psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 41 publications
(59 reference statements)
2
56
0
Order By: Relevance
“…Behavioural observation captured changes in well-being ( Kinney & Rentz, 2005 ; Gross et al, 2013 ; Rentz, 2002 ; Sauer, Fopma-Loy, Kinney, & Lokon, 2016 ) and in engagement ( MacPherson, Bird, Anderson, Davis & Blair, 2009 ) . Roe et al (2016) took a more subjective, ethnographic approach with their observation, qualitatively analysing the researcher’s fieldwork notes from the arts sessions, as did Huzzan et al (2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural observation captured changes in well-being ( Kinney & Rentz, 2005 ; Gross et al, 2013 ; Rentz, 2002 ; Sauer, Fopma-Loy, Kinney, & Lokon, 2016 ) and in engagement ( MacPherson, Bird, Anderson, Davis & Blair, 2009 ) . Roe et al (2016) took a more subjective, ethnographic approach with their observation, qualitatively analysing the researcher’s fieldwork notes from the arts sessions, as did Huzzan et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, one of the art-making programmes (Memories in the Making) delivered in three studies ( Kinney & Rentz, 2005 ; Rent, 2002; Gross et al, 2013 ) explicitly encouraged to talk about memories the paintings stirred , w ith some well-being outcomes captured. Others, although not focussing on reminiscence for memory, suggested that participants recalled some memories.…”
Section: Resultsmentioning
confidence: 99%
“…Although there has been an increasing interest in exploring well-being for people with dementia in arts projects (Gross, Danilova, & Vandehey, 2015, Osman, Tischler, & Schneider, 2016, Windle et al, 2017), there is a dearth of research that has focused on the capacity for agency in these contexts. This is understandable given a contemporary context that ‘gives’ the arts to people with dementia and assumes that dementia necessarily involves a loss of self and identity (Hughes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Those above-mentioned interventions are predominantly conducted in controlled environments in line with detached observations, interviews and surveys in order to precisely measure and analyze the cause and effect of the experiments. It is no wonder that this outcome-centered approach exposes a significant gap in “the more mundane ordinary forms of creativity” (Bellass et al 2019 :2) “beyond the temporal boundaries” of the events (Gross et al 2015 :31).…”
Section: Arts Affective Creativity and Couplesmentioning
confidence: 99%